Thinking about developmental statehood, manufacturing and international capital: the case of Ethiopia. Issue 2 (3rd April 2022) - Ikpe, Eka
ABSTRACT: The developmental state paradigm (DSP) has traversed global south contexts from Latin America to Asia with a revival in African contexts. However, there is limited understanding of how international political economy (IPE) dynamics influence the analysis offered by the DSP. This article addresses this gap by introducing an IPE-enhanced DSP that centres interactions between the state and international capital in the analysis of industrialisation in the Ethiopian leather subsector and the role of Chinese investment. Its key finding is that these complex interactions influence and disrupt the classical roles of domestic private capital and domestic industrial demand in socio-economic transformation.